Patient knowledge and information-seeking about personalized cancer therapy. (April 2016) - Rogith, Deevakar; Yusuf, Rafeek A.; Hovick, Shelley R.; Fellman, Bryan M.; Peterson, Susan K.; Burton-Chase, Allison M.; Li, Yisheng; Bernstam, Elmer V.; Meric-Bernstam, Funda
Highlights: Female breast cancer patients completed a self-administered questionnaire. Cancer genetics and personalized cancer therapy knowledge was moderate. Only 27% of patients indicated that they had sought information regarding PCT. Education and income were associated with higher knowledge scores and information-seeking. Knowledge was not associated with willingness to participate in research. Abstract: Background: Understanding patients' knowledge and prior information-seeking regarding personalized cancer therapy (PCT) may inform future patient information systems, consent for molecular testing and PCT protocols. We evaluated breast cancer patients' knowledge and information-seeking behaviors regarding PCT. Methods: Newly registered female breast cancer patients ( n = 100) at a comprehensive cancer center completed a self-administered questionnaire prior to their first clinic visit. Results: Knowledge regarding cancer genetics and PCT was moderate (mean 8.7 ± 3.8 questions correct out of 16). A minority of patients (27%) indicated that they had sought information regarding PCT. Higher education ( p = 0.009) and income levels ( p = 0.04) were associated with higher knowledge scores and with seeking PCT information ( p = 0.04). Knowledge was not associated with willingness to participate in PCT research. Conclusion: Educational background and financial status impact patient knowledge as well as information-seeking behavior. For most patients, clinicians are likely to be patients' initial source of information about PCT. Understanding patients' knowledge deficits at presentation may help inform patient education efforts.